Implementation of Criminal Execution of Tax Fines Against Decision Number: 249/PID.SUS/2022/PN. TPG - Putunezar, Shaeku; Nurlaily, Nurlaily; Disemadi, Hari Sutra (PAMALI: Pattimura Magister Law Review, 2025)
Introduction: Taxes are obligations requiring citizens to pay a specified amount of money to the state. Following the enactment of the Tax Harmonization Law in 2021, tax law enforcement in Indonesia has been directed toward recovering state revenue losses.Purposes of the Research: This study aims to describe and analyze the implementation of criminal fine execution in tax cases as outlined in Decision Number: 249/Pid.Sus/2022/PN.Tpg.Methods of the Research: The study employs a normative legal approach through library research, which includes references such as laws, articles, and journals. Secondary data were collected through literature review and analyzed using a qualitative juridical approach.Results Main Findings of the Research: The findings of the study show that the confiscation of land and buildings belonging to the convicts is not in line with Article 39 Paragraph (1) of the Criminal Procedure Code. In addition, the assets had been used as collateral by Bank Mandiri Tanjungpinang, a State-Owned Enterprise, before the investigation began. This results in a lack of legal certainty and becomes an obstacle in the execution process. To ensure legal certainty, the investigation process must be accompanied by the tracking and blocking of the assets found, in the settlement of tax criminal cases in Decision Number: 249/Pid.Sus/2022/PN.Tpg, deliberation or coordination regarding land and building assets can be carried out, because the ultimate goal is to return the results of the execution to the state.